Private Participation in Energy - Izaguirre, Ada Karina (World Bank, Washington, DC, 2012)
From 1990 to 1999 there were 700 energy projects in developing countries involving private participation. Investment in these projects totaled nearly US$190 billion, and foreign capital was a major source of funds. Global developers were the top ten sponsors of private energy projects in developing countries. Their projects accounted for just over a third of total investment. This Note surveys the trends by region, by country income level, and by type of project. It also explores the consequences of the recent Asian financial crisis for future investment in Asian energy markets.